Role of codoping on multiferroic properties at room temperature in BiFeO3 ceramic - Ghosh A.K.; Dwivedi G.D.; Chatterjee B.; Rana B.; Barman A.; Chatterjee S.; Yang H.D. (My University, 2025)
Role of codoping (20% La in Bi-site and 10% Mn in Fe-site) on mutiferroic properties in insulating BiFeO3 ceramic have been investigated. The X-ray diffraction (XRD) with Rietveld refinement shows that the structure of Bi0.8La0.2FeO3 is orthorhombic (Pnma). Furthermore, it shows that on substitution of 10% Mnions in Fe-site, no structural change occurs which has been supported by micro-Raman study. DTA study shows that ferroelectric transition temperature (TC) decreases very fast due with La-doping and slowly with the Mn-doping. Measurement on magnetization vs. applied magnetic field (M-H) shows increase of magnetization due to codoping of La and Mn in BiFeO 3. This may be due to partly destruction or suppression of the spin cycloid structure in it and/or the introduction of the mixed valance state. P-E measurement shows high leakage in Bi0.8La0.2Fe0.9Mn0.1O3. © 2013 Elsevier Ltd. All rights reserved.